ANALISIS LAGU BERTEMA AKUNTANSI “GALANG RAMBU ANARKI” DALAM PERSPEKTIF SEMIOTIKA ROLAND BARTHES - Shirleen, Jessica Patrisia; Puspitasari, Ayu; Hijriah, Amanah (Jurnal Kewirausahaan Bukit Pengharapan, 2023)
The main purpose of this research is to deconstruct the meaning and motivation behind the Accounting-themed song "Galang Rambu Anarki." This is an interpretive qualitative study based on Roland Barthes' semiotic approach. Document analysis is used as a data collection technique. The data was analyzed in three ways: denotative meaning, connotative meaning, and myth. According to the findings of this study, the song "Galang Rambu Anarki" contains all three aspects of Roland Barthes' semiotics. The denotative meaning of this song conveys the difficulties caused by inflation, such that the children identified as "Galang" are malnourished. The songwriter interprets the connotative meaning of this song as the relationship between common people and the country's leaders, and the myth in this song contains a message that financial difficulties are not an impediment to building a better life in the future.